Pengaruh Modal Manusia Terhadap Kemiskinan di Indonesia - Lorenza Gusrima Trisni; Amar, Syamsul (Universitas Negeri Padang, 2024)
This study was conducted to identify the effect of education and health on poverty in Indonesia. The object of this research is 34 provinces in Indonesia in 2013 - 2022 which are processed using Eviews 12 software. Based on the analysis that has been carried out based on the overall regression results, the research results show that partially education has a significant effect on poverty in Indonesia and health has a significant effect on poverty in Indonesia.